A Literature Review of Research on China’s Monetary Policy and Debt Leverage - Lin, Jiaming (Journal of Accounting, Business and Finance Research, 2019)
One of the problems of China’s economic transformation is the high debt leverage，the call for deleveraging has become one of the hottest issues in recent years. The existing researches have discussed extensively the level and structure of China’s debt leverage, as well as its impact on financial stability. This paper mainly reviews the impact of monetary policy and tools on the debt leverage, in order to research the debate of "Loosing deleverage" or "tightening deleverage". We think that the structural problems of debt leverage should be adjusted by structural monetary policy. Monetary policy regulation cannot be a decisive factor in reducing high debt leverage. Clarifying the influence mechanism and path of monetary policy regulation, we can prescribe the right medicine. In the process of steadily deleveraging, we should also pay attention to the sustainability of debt. Therefore, using monetary tools to steadily deleverage is not a loose or tight policy choice, but an orderly guidance of all macroeconomic sectors on the basis of maintaining a sound monetary policy.